Determining the Views of Music Teachers at BILSEMs on the Music Field Student Diagnosis Process: The Case of Bursa - Sakin, Ajda Şenol; Özer, Zeynep (Journal of Education in Black Sea Region, 2021)
Science and Art Centers (BILSEM) are state institutions in Turkey operating under the Ministry of National Education, which aim to ensure that gifted students in Turkey acquire a scientific study discipline and develop their creativity in line with their talents and interests. In these centers, there are three different special talent fields: music, visual arts and general talent. In this study, it was aimed to determine the views of music teachers working at Science and Art Centers (BILSEM), which are activity-based centers where gifted students in Turkey receive education, about the student diagnosis process of music field. Music teachers working at BILSEM in the city center and districts of Bursa participated in the study. The study is in the case study research design, one of the qualitative research methods. The data were obtained using a semi-structured interview form. The acquired data were analyzed using the directed content analysis method. In this direction, 5 themes and 34 codes were determined. In the study, most of the teachers stated that group (Tablet) scanning application for the student diagnosis process was not necessary for prospective music students, that the content and criteria of the questions related to aural skills and memory should be changed and that the content related to the field of musical awareness was insufficient and needed to be improved. In addition, the music teachers evaluated the conditions of the exam environment and expressed different opinions on the subject. At the end of the study, various suggestions were made on the subject in the light of the obtained data and evaluations. Key words: BILSEM, centers for gifted students, diagnosis, music course, gifted students